1993
DOI: 10.1159/000247323
|View full text |Cite
|
Sign up to set email alerts
|

Diflorasone Diacetate Ointment 0.05% versus Betamethasone Dipropionate Ointment 0.05% in Moderate-Severe Plaque-Type Psoriasis

Abstract: We report the results of a 2-week double-blind, parallel clinical trial comparing two superpotent topical glucocorticosteroid ointments, diflorasone diacetate 0.05% and betamethasone dipropionate 0.05%, in psoriatic adults. Both corticosteroid ointments were fast acting and highly efficacious. 40 of the 44 patients who initially enrolled completed the trial. There were no statistically significant differences between the two glucocorticoids with respect to erythema, scaling, induration or the investigator’s gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…The shortest length of treatment was one week. Treatment success with betamethasone dipropionate 0.05 mg/g ointment 2X/daily was seen after two to three weeks; marked improvement was seen after only one week [117, 124, 137]. The efficacy of beta‐ methasone dipropionate is confirmed by all studies; studies report significant improvement or complete clearance after two to four weeks in 25 – 77.8%[126, 141].…”
Section: Topical Therapymentioning
confidence: 99%
“…The shortest length of treatment was one week. Treatment success with betamethasone dipropionate 0.05 mg/g ointment 2X/daily was seen after two to three weeks; marked improvement was seen after only one week [117, 124, 137]. The efficacy of beta‐ methasone dipropionate is confirmed by all studies; studies report significant improvement or complete clearance after two to four weeks in 25 – 77.8%[126, 141].…”
Section: Topical Therapymentioning
confidence: 99%
“…Ten grade A 2 studies on topical steroid monotherapy were included [116][117][118][119][120][121][122][123][124][125], 17 grade B studies [104,[126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141], and two grade C studies [142,143]. Ten grade A 2 studies on topical steroid monotherapy were included [116][117][118][119][120][121][122][123][124][125], 17 grade B studies [104,[126][127][128][129][130][131][132][133][134]…”
Section: Efficacymentioning
confidence: 99%
“…data]. The corticosteroid chosen was betamethasone dipropionate, as it is widely used for the treatment of psoriasis and its efficacy and safety are well established [12, 13, 14]. Two large studies [15, 16]have demonstrated the superior efficacy of this new combination treatment used twice daily compared to twice daily application of its individual active components.…”
Section: Introductionmentioning
confidence: 99%